1956
DOI: 10.1149/1.2430231
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Refractory Silicides with Carbon and Nitrogen

Abstract: The s ilic id e s of T i, Z r, Ce and Nb were Investigated to determine the phases present a t tem peratures around 2000*K* The m o tio n s o f s ilic id e s of T i, Z r, Ce, Nb, Ta, Ho and V with earbon were studied a t these tempera tu re s * Also a U n ited amount of work was dons on the reactions o f some of the s ilic id e s with nitrogen* The data have been used to estab lish tern ary phase diagrams for the systems and to obtain upper and lower lim its fo r the heats o f formation of the silic id e s * T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

1959
1959
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 144 publications
(18 citation statements)
references
References 13 publications
2
16
0
Order By: Relevance
“…However, the stoichiometry of Ta 4.5 Si was not firmly established in their work. Brewer and Krikorian [18] suggested that Ta 4.5 Si was a metastable crystalline phase, which was later confirmed by Deardorff et al [19] A new compound, Ta 3 Si, was further identified by x-ray diffraction (XRD). [19,20] Kocherzhinskii et al [21] carefully measured the phase diagram of the Si-Ta system using metallographic, XRD, and differential thermal analysis (DTA) techniques.…”
Section: The Si-ta Systemmentioning
confidence: 89%
See 1 more Smart Citation
“…However, the stoichiometry of Ta 4.5 Si was not firmly established in their work. Brewer and Krikorian [18] suggested that Ta 4.5 Si was a metastable crystalline phase, which was later confirmed by Deardorff et al [19] A new compound, Ta 3 Si, was further identified by x-ray diffraction (XRD). [19,20] Kocherzhinskii et al [21] carefully measured the phase diagram of the Si-Ta system using metallographic, XRD, and differential thermal analysis (DTA) techniques.…”
Section: The Si-ta Systemmentioning
confidence: 89%
“…Most experimental work showed that the solubility of Ta in Si was negligible. [16][17][18][19][20][21] By means of direct-reaction calorimetry, Robins and Jenkins [23] measured the enthalpies of formation of aTa 5 Si 3 (À39.7 kJ/mol) and TaSi 2 (À14.4 kJ/mol) at ambient temperature. Myers and Searcy [24] determined the Gibbs energies of formation (D f G) of four compounds using Knudsen effusion cells.…”
Section: The Si-ta Systemmentioning
confidence: 99%
“…Temperature is, however, a limiting factor, because this compound WC reacts with W at 1420 K to form W 2 C, which is not stable in the presence of SiC. [27] As a consequence, this carbide can only be used up to 1420 K. The carbon mobility in these two compounds has to be established. …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, silicon carbide is a very interesting material for several high-temperature applications; nevertheless, this compound reacts with metals. [1][2][3][4][5][6][7][8][9][10][11][12] In this way, the research of diffusion barriers, limiting diffusion of fast-moving elements such as carbon and silicon, is particularly important. Only a small amount of data about this particular point can be found in the literature; it is also difficult to predict the growth of such a kind of layer.…”
mentioning
confidence: 99%
“…[11][12][13][14][15] However, possibilities of solidstate reactions between SiC and refractory materials have substantial interest. For W alloy, thermal reactions between SiC and W have been reported by many researchers; Luo et al, [16] Roger et al, [17] Brewer and Krikorian, [18] and Baud et al [19] Even though SiC was attempted to use as a diffusion barrier in their researches, W and SiC were reacted and formed W-silicides under the high-temperature annealing. Especially according Luo et al, [16] strength degradation of the fiber was reported because of the W/SiC interface reaction at 1 000 C. In order to enhance the thermal stability of W with SiC, the addition of less reactive material can be an effective approach.…”
Section: Introductionmentioning
confidence: 99%